Green Chemistry Education at the Secondary School Level: A Bibliometric Analysis of Trends and Research Gaps - Syahrul Bachtiar; Dwi Ajni Shafarwati (Hydrogen: Jurnal Kependidikan Kimia, 2026)
Green Chemistry Education (GCE) has become increasingly important in supporting sustainability-oriented chemistry learning at the secondary school level. This study aims to map research trends, identify dominant themes, and examine research gaps in GCE through a bibliometric analysis. The final dataset consisted of 43 articles retrieved from the Scopus and Web of Science databases for the period 2016–2025. Data were analyzed using VOSviewer through keyword co-occurrence and thematic mapping. The findings show a growing scholarly interest in GCE, reflecting the increasing relevance of sustainability principles in chemistry education. Keyword analysis indicates that existing studies are mainly centered on students, teachers, education systems, active learning, experimentation, and contextual learning approaches. The thematic development also shows a shift from foundational discussions of green chemistry principles toward curriculum integration, digital learning innovation, ethnochemistry, and alignment with the Sustainable Development Goals (SDGs). Despite this development, several gaps remain, particularly in long-term impact evaluation, students’ behavioral change, teacher preparedness, and interdisciplinary implementation. This study contributes by providing a structured overview of the GCE research landscape in secondary education and by offering directions for educators, policymakers, and researchers to strengthen sustainable chemistry learning.